Assessment of Overall Self-Care Among the East Indian Population: An Experimental, Observational, and Validated Study - Partha Sarathi Biswas; Mohammad Jalaluddin; Poulami Sarangi; Somen Bagchi (Oral Sphere Journal of Dental and Health Sciences, 2025)
Introduction: Sleep hygiene of college students’ habits and practices in the environmental setting that promote good sleep tends to go unnoticed, leading to poor quality of sleep and poorer academic performance. The current research was conducted with the aim of evaluating knowledge, attitude, and practices (KAP) of students of Srinivas College of Pharmacy, Mangalore regarding sleep hygiene and academic performance. Methods: A cross-sectional online survey among 289 students (53.98% female) was carried out in the form of a structured internet questionnaire during January to April 2025. Information on KAP regarding sleep hygiene was collected and presented with descriptive statistics in the form of frequencies, percentages, and 95% CIs. Results: There was moderate awareness with 63.7% being aware of sleep hygiene and 74.7% being aware of sleeping-conducive habits but only 34.6% actually knowing 8–9 hours as recommended sleeping time. The majority (83.4%) believed school required sleep, and 97.6% related stress to bad sleep. Nevertheless, 51.2% slept only 4–6 hours on college nights, and 85.1% used electronic media prior to bedtime. Unexpectedly, 77.5% admitted having dozed off in school, and 96.2% thought sleep loss impaired concentration. Conclusion: There is clear lack of connection between information and action. Learning alone will not do the interventions to reduce screen use and change sleeping habits are required to ensure enhanced school performance.